The Influence of Brain Rot on Speaking Learning Strategies among Junior High School Students - Sari, Risma Novita; Hastuti, Purwanti Widhy; Herda, Rozanah Katrina; Ivashova, Elizaveta Evgenievna (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2026)
The massive growth of technology has transformed the learning environment for young generations. This (new) learning environment offers both benefits and challenges, such as brain rot phenomenon. Brain rot refers to cognitive decline, resulting from excessive screen time and overconsumption of short-duration content. Thus, this study examines whether brain rot affects speaking learning strategies among junior high school students, who are part of Gen Alpha and born as digital natives. A mixed-methods approach was applied, involving 64 students who completed questionnaires, followed by interviews with six participants. The findings indicate that students’ brain rot levels are generally low to moderate, while their speaking learning strategies are at moderate levels, with higher use of metacognitive and socio-affective strategies compared to cognitive strategies. Linear Regression analysis shows that brain rot has a significant and negative effect on speaking learning strategies, explaining 19.6% of the variance. The interviews confirm that excessive screen time leads to cognitive fatigue and cognitive load. These results highlight the need for teachers and parents to monitor students’ digital media use.